Implementasi Model Pembelajaran Menggunakan Alat Peraga Peta untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran IPS - Putu Eka Juliana Jaya (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2020)
This class action research aims to analyze the implementation of learning models using visual aids to improve student learning outcomes in class VIII F in social science subjects at SMP Negeri 1 Denpasar. The research subjects were 48 students of class VIII F. The data used in this study were primary data and secondary data. The research procedure was carried out by applying the creation and use of the map props, which consisted of 2 cycles. The steps taken in each cycle are: planning, action and reflection, observation. Data Collection Techniques use observation, written evaluation, and documentation techniques. Data analysis was carried out qualitatively and quantitatively. Based on the results of data analysis on increasing learning activities from a total of 48 students of class VIII F SMP Negeri 1 Denpasar: Increased learning outcomes from a total of 48 students of class VIII F SMP Negeri 1 Denpasar, which in the initial conditions average score 68.54 with classical learning completeness as many as 19 students or 39.58%, increasing in the first cycle to 39 students or 81.25% with an average value of 78.75 and finally in the second cycle increased again to 87.50 at an average value of 100% completeness .